Hybridising inorganic materials with fluorescent BOPHY dyes: A structural and optical comparative study - Sani, Umar; Alatawi, Omar M.; Halawani, Nuha M.; Gould, Jamie A.; Knight, Julian G.; Cucinotta, Fabio (Frontiers in Chemistry, 2022)
This study presents the design and characterization of new monochromatic light-harvesting systems based on inorganic porous materials hybridized with organic dye molecules within their structure. A new fluorescent BOPHY dye was prepared, characterized optically and used as both reference and synthetic precursor for two alkoxysilane derivates that were incorporated separately within a silica structure. The dyes, one bearing one alkoxysilane group and the other one two, were co-condensed with tetraethyl orthosilicate to from a hybrid organosilica framework, where they are found at specific locations. The structure of the new materials was analysed by powder XRD and TEM, which confirmed the presence of the hexagonal pore arrangement typical of mesoporous MCM-41 silica particles. The steady-state and time-resolved analysis showed that the particles where the dyes are most dispersed within the framework retain the highest fluorescence, up to 0.63, in the green-yellow region of the visible spectrum. On the other hand, increasing the content of BOPHY units in the solid matrix seem to favour non-radiative deactivation pathways and aggregation phenomena, which lower the efficiency of light emission. The materials also exhibit interesting properties, such as a dual excited-state decay and fluorescence anisotropy. The short fluorescence lifetime, about 2 ns, matches the typical singlet lifetime of BOPHY dyes, whereas the long component, up to 20 ns, is attributed to delayed fluorescence, which could take place via charge recombination. Optical anisotropy experiments revealed that all materials show polarised light emission to a significant extent and, for most samples, it was also possible to determine a polarisation transfer decay trace, from 400 to 800 ps. This is ascribed to the occurrence of energy migration between neighbouring dye units within the silica structure.